Characterization of Mixed Farming Systems in Ethiopia: Mixed Farming Systems (MFS) Initiative Baseline Evaluation Survey Report - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
The Sustainable Intensification of Mixed Farming Systems (SI-MFS) is a global research and development initiative launched by CGIAR to enhance smallholder farmers' livelihoods. SI-MFS aims to increase food security, nutrition, and income for vulnerable communities by focusing on mixed farming systems. The initiative has three key objectives: equitable approaches, livelihood improvement, and evidence-based innovation. For the first key objective, the SI-MFS initiative seeks to provide equitable and gender-transformative solutions. It recognizes the diverse roles of men and women in agriculture and aims to empower both genders while the initiative targets smallholder farmers engaged in mixed farming across six countries, including Ethiopia, Ghana, Malawi, Laos PDR, Bangladesh, and Nepal, under the second key objective. The initiative emphasizes evidence-based, validated, sustainable intensification practices in the last key objective. These practices are designed to maximize synergies and minimize trade-offs between farming systems' biophysical and social components.